Approaches to Student Evaluation in Invention Pedagogy - Saarinen Auli; Lavonen Jari (Routledge, 2025)
This chapter introduces approaches for the evaluation of students’ learning process and learning outcomes during an invention project. Based on various pieces of research in the field, the authors recommend that diagnostic, formative, summative, self, and peer-evaluation practices should be emphasized as a part of the evaluation of an invention project. These practices support and supplement each other. Furthermore, the teacher’s role in an evaluation of an invention project is analyzed and examples of the learning processes (formative evaluation) and outputs (summative evaluation) are introduced and discussed. Special emphasis is placed on the use of the digital portfolio as a tool for evaluating the design process and knowledge building. Finally, the use of ePortfolio is discussed and further its adequacy for the nonlinear learning process analyzed.
Invention Pedagogy – The Finnish Approach to Maker Education